Sudden cardiac death: an update. Issue 7 (11th July 2019) - Isbister, Julia; Semsarian, Christopher
Abstract: Sudden cardiac death (SCD) is a devastating and all too common result of both acquired and genetic heart diseases. The profound sadness endured by families is compounded by the risk many of these deaths confer upon surviving relatives. For those with known cardiac disease, disease‐specific therapy and risk stratification are key to reducing sudden death. For families of a SCD victim, uncovering a definitive cause of death can help relieve the agonising uncertainty and is a vital first step in screening surviving relatives and instituting therapy to reduce SCD risk. Increasing knowledge about the molecular mechanisms and genetic drivers of malignant arrhythmias in the diverse clinical entities that can cause SCD is vital if we are to optimise risk stratification and personalise patient care. Advances in diagnostic tools, disease‐specific therapy and defibrillator technology are improving outcomes for patients and their families but there is still much progress to be made.